Acute and delayed responses of C-reactive protein, malondialdehyde and antioxidant markers after resistance training session in elite weightlifters: Effect of time of day - Ammar, A.; Chtourou, H.; Hammouda, O.; Trabelsi, K.; Chiboub, J.; Turki, M.; Abdel Karim, O.; El Abed, K.; Ali, M. B.; Hoekelmann, A.; Souissi, N. (Chronobiology International, 2015)
The aim of this study was to investigate the effect of an Olympic-Weightlifting-session followed by 48-h recovery period on the oxidative and antioxidant parameters` diurnal variation. Nine weightlifters (21 ± 0.5 years) performed, in randomized order, three Olympic-Weightlifting-sessions at 08 h:00, 14 h:00 and 18 h:00. Blood samples were collected: at rest and 3 min and 48 h after each session. C-reactive protein (CRP), rate of lipid peroxidation and antioxidant activities were assessed. At rest, analysis of variance showed a significant time of day (TOD) effect (p < 0.05) for uric acid, catalase and glutathione peroxidase with higher values at 14 h:00 and 18 h:00 compared with 08 h:00. However, no significant TOD effect for malondialdehyde, total bilirubin and CRP was observed. Given the profound changes (p < 0.001) in the post-training session values, these diurnal variations have been altered immediately and even 48 h after the training sessions. Despite the significant decreases in the post-training values after the 48-h recovery period (p < 0.05), levels of lipid peroxidation and enzymatic defense remained elevated (p < 0.05) 48 h after the morning training session. However, after the afternoon and evening sessions, the same period was sufficient to return values to the baseline levels. In conclusion, the morning session seems to generate the most important acute and delayed lipid peroxidation responses. Therefore, weightlifting coaches should avoid scheduling their training sessions in the morning-hours.